On the Most Innovative Outer Access Structure of any Bantu Dictionary: The Lexique kikongo–franÃ§ais by Charles Polis (1938) - de Schryver, Gilles-Maurice (Lexikos, 2015)
In this article a little-known dictionary manuscript from the 1930s, the Lexique kikongo-français by the Jesuit missionary Charles Polis, is analysed in great detail. Section 1 expounds on the goal and raison d'être of the study, Section 2 introduces the manuscript, its author as well as the Kikongo variety dealt with, Section 3 presents the inner workings of the Lexique on macro-, micro- and mediostructural levels, Section 4 gives a lexicographical appreciation based on a large selection of the entries, Section 5 joins the international debate on the exact nature of a dictionary's macrostructure, access structure and access route, and Section 6 compares Polis's work with a dictionary from the same region and period. Conclusions are offered in Section 7, chief among them the fact that Polis designed the most innovative outer access structure of any Bantu dictionary.